Overview of Physical Activity in Elderly People with Hypertension in Ngemplak District, Boyolali Regency - Nirmala, Annisa Rosie; Prajayanti, Eska Dwi (INDOGENIUS, 2025)
Background & Objective: Older adults experience physiological changes, including in the cardiovascular system, which can potentially cause hypertension. In Central Java Province, the prevalence of older adults reaches 15.46%, while in Boyolali District there are 14.83% or 160,188 people aged over 60 years. Physical activity plays an important role in controlling blood pressure and preventing complications of hypertension, but many elderly people have low to moderate levels of physical activity. This study aims to describe the level of physical activity in elderly people with hypertension in Ngemplak Subdistrict, Boyolali Regency. Method: A quantitative descriptive method was used with 92 elderly respondents selected using accidental sampling. The research instrument was the GPAQ (Global Physical Activity Questionnaire) from the WHO. Data collection was conducted on June 9, 2025, in the Ngemplak Community Health Center working area. Result: The results showed that 52.17% of respondents had a moderate level of activity, 31.52% had a light level, and 16.30% had a heavy level. Conclusion: The conclusion of this study is that the majority of elderly people with hypertension in the area have moderate physical activity. These findings are expected to be a reference for health workers in designing promotion and education programs, as well as motivating the elderly to increase regular physical activity to prevent worsening hypertension.